Energy is at the root of Australia's political crisis: building a resilient renewable grid. Issue 4 (26th November 2019) - Hart, Paul
Abstract : Renewable energy sources are becoming more abundant as costs fall and climate change becomes ever more influential in decision making. One drawback of renewable energy sources is that they tend to rely on environmental factors, making them unreliable when powering a 24/7 society. One solution to the storage of energy is reservoirs. While the technology has been around for decades, the business case is often difficult to define or prove. The Australian Renewable Energy Agency together with Australia National University, Black & Veatch and a team of specialists, developed tools which identify potential locations, produced a high-level assessment of required infrastructure, and developed a cost model on which site-selection decisions can be made. In doing so they have created a catalogue of potential sites that can be developed across Australia, ready to help the energy grid provide for the twenty-first century.